A comparing key performance indicator and benchmarks of quality pre-school among the agency in Malaysia - Nordin Mamat; Abdul Rahim Razali; Abdul Talib Hashim; Mohd Mahzan Awang; Mohamed Nor Azhari Azman; Nur Fajrie (International Journal of Evaluation and Research in Education (IJERE), 2023)
High quality early childhood education (ECE) enables children to enjoy the experience and have nurturing environment that promotes holistic development. The key performance indicators such as quality pre-school’s environment, teachers and assistant teachers, learning materials have been predicted to produce desirable outcomes. However, the challenge is to identify the predictors that can quantify the definition of a quality teacher. This study uses questionnaire to assess individual perceptions and views on quality key performance indicators of early childhood pre-school center. The study’s findings revealed that the gap analysis related to the qualification of pre-school teachers and ratio teacher-child below the standard. Even though teacher-child ratio in private pre-schools is small because most of pre-schools do not employ assistant teacher as practiced in other pre-schools. Thus, the study found that the performance of children’s abilities in Ministry of Education pre-school and private pre-schools exceeded the national standard of 76.2% National Average of Reading and Writing, and 64.6% National Average of Arithmetic. However, based on benchmark 100% achievement, the screening performance report shown children far left behind. In conclusion, these findings are important to be given attention and remedial action in order the improvement and quality of pre-school achieve the minimum standard.